Statistical literacy of Slovak lower secondary school students - Jurečková, Mária; Lucia Csachová, (Technium Social Sciences Journal, 2020)
The article is focused on monitoring the level of statistical literacy of 9th grade students at lower secondary schools in the Slovak Republic. The results of several years testing of students were used for this purpose. During the reporting period, more than 50 000 pupils from all over Slovakia participated in the testing. In addition to quantitative data analysis, attention is also paid to qualitative analysis of the problems in the field of statistics that were difficult for students. The article presents a part of the results of the research focused on the analysis of critical points in school mathematics.